COMPETITION-BASED GROUP QUIZ UNTUK LEARNING MANAGEMENT SYSTEM MOODLE - “Prama Ade Prayitno; Komang Oka Saputra; Ni Made Ary Esta Dewi Wirastuti (Program Studi Teknik Elektro UNUD, 2022)
Quizzes are used by teachers in the learning evaluation process which aims todetermine the extent of mastery of the material provided by the teacher to students. The quizconsists of several items about which are carried out directly by students. In this study, thisresearch was carried out online by students in groups using a Learning Management System(LMS), namely Moodle with the help of a plugin. The result of the work is that the availability ofthe current score only produces 1 and then these values are to be developed for each studentin the same group. This resulted in the evaluation process of learning in the quiz to be less fairBased on this problem, a plugin that can process is created that can process from workbased on personal views generated by students. The personal score is then used to calculatethe score by taking the average of all students in the group. Furthermore, the final valueobtained from the calculation of the ratio of personal values to group values. This final score willbe used to evaluate learning in the use of quizzes using Moodle. The results of the study aftertesting the system usability scale (SUS) showed that plugins that had good feasibility andblackbox testing methods declared the plugin well.